The Impact of the Pandemic Covid-19 on the Human Right to Freedom of Movement - Zolka, Valentyn; Tsarenko, Olha; Kushnir, Iryna; Tsarenko, Serhii; Havrik, Roman (European Journal of Sustainable Development, 2021)
The article discusses the impact of the pandemic COVID-19 on the human rights, in particular, the right to freedom of movement and free choice of residence. The purpose of the article is to investigate whether the restrictions implemented to prevent spread of the infection were legitimate and necessary. The concept and content of the right to free movement according to Ukrainian legislation has been investigated. The legitimate grounds for restriction of human rights were analyzed. The state of compliance of Ukrainian legislation with the legislation of the EU and world standards was revealed. The range of issues that Ukraine faced during the pandemic COVID-19 and limitations of human rights were disclosed. Particular attention was paid to legal acts which implemented such limitations. It was revealed that the approach of the Ukrainian legislator while implementing restrictions of human rights was unconstitutional and violated fundamental human freedoms. General and special scientific methods were used in the process of research, such as dialectical, comparative, dogmatic and legal methods.